Distribution and climatological trajectories of plastic debris released from the major rivers along the east coast of India using the Lagrangian particle tracking model - M. Pruthvi Raju; V. Suneel; S. Veerasingam; P. Suneetha; Surireddi Satya Venkata Siva RamaKrishna (Environmental Monitoring and Assessment, 2025)

Smart technologies in aquaculture: An integrated IoT, AI, and blockchain framework for sustainable growth - Prince Jebedass Isaac Chandran; Hana Ahmed Khalil; PK Hashir; Veerasingam S (Aquacultural Engineering, 2025)

Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha; S. Veerasingam; S. Rajendran; Hassan Hassan; Muhammad Zia U. R. Rahman Hashmi; Hamood Alsaadi; Nelson Rangel-Buitrago; Fadhil N. Sadooni (Environmental Monitoring and Assessment, 2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (I g ₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf.

A comprehensive review of urban microplastic pollution sources, environment and human health impacts, and regulatory efforts - Jin-Yong Lee; Rogers Wainkwa Chia; S. Veerasingam; Saif Uddin; Woo-Hyun Jeon; Hee Sun Moon; Jihye Cha; Jejung Lee (Science of The Total Environment, 2024)

PAHs and hopanes in the surface sediments of Qatar coast and their ecological risks: Comparison with regional and global coastal regions - Samah Dib; S. Veerasingam; Thoraya Alyafei; Mazen Abou Assali; Jassim Al-Khayat; P. Vethamony (Marine Pollution Bulletin, 2024)

Contributions of Fourier transform infrared spectroscopy in microplastic pollution research: A review - S. Veerasingam; M. Ranjani; R. Venkatachalapathy; Andrei Bagaev; Vladimir Mukhanov; Daria Litvinyuk; M. Mugilarasan; K. Gurumoorthi; L. Guganathan; V. M. Aboobacker; P. Vethamony (Critical Reviews in Environmental Science and Technology, 2021)

Identification and characterization of tsunami deposits off southeast coast of India from the 2004 Indian Ocean tsunami: Rock magnetic and geochemical approach - S Veerasingam; R Venkatachalapathy; N Basavaiah; T Ramkumar; S Venkatramanan; K Deenadayalan (Journal of Earth System Science, 2014)

Environmental magnetic and geochemical characteristics of Chennai coastal sediments, Bay of Bengal, India - R VENKATACHALAPATHY; S VEERASINGAM; N BASAVAIAH; T RAMKUMAR; K DEENADAYALAN (Journal of Earth System Science, 2011)

Petroleum hydrocarbon concentrations in ten commercial fish species along Tamilnadu coast, Bay of Bengal, India - S. Veerasingam; R. Venkatachalapathy; P. Raja; S. Sudhakar; V. Rajeswari; R. Mohamed Asanulla; R. Mohan; P. Sutharsan (Environmental Science and Pollution Research, 2011)

Petroleum Hydrocarbon Concentrations in Marine Sediments Along Chennai Coast, Bay of Bengal, India - R. Venkatachalapathy; S. Veerasingam; T. Ramkumar (Bulletin of Environmental Contamination and Toxicology, 2010)